Prácticas de enseñanza del área de lengua y literatura en el segundo año de educación general básica del Centro Escolar Eloy Alfaro - Cevallos Guevara, José Luis (2016)
A good teacher performance is fundamental in the second year of basic education, especially in the area of Language and Literature, where skills of oral and writer communication are developed. Most of the times teachers can not apply the method logical processes, because of the huge number of students, in just one classroom. In the present research is analyzed the teaching techniques of Language and Literature in the Second Year "A" of EGB School Eloy Alfaro Center, this is based on direct observation of the classes by the respective teacher are analyzed. This teaching technique was affected by the constant change of teachers and lack as their lack of experience who was designated for this year of basic, who did not known about teaching practices, that is the reason of why the contribution was not the expected.